# How do you solve #9 - 3x = 36#?

x = -9

Add 3x to both sides of the equation and also subtract 36 from both sides. One gets -27 = 3x or, equivalently, -9 = x.

By signing up, you agree to our Terms of Service and Privacy Policy

To solve 9 - 3x = 36, first, isolate the variable term by subtracting 9 from both sides:

9 - 3x - 9 = 36 - 9 -3x = 27

Next, divide both sides by -3 to solve for x:

-3x / -3 = 27 / -3 x = -9

By signing up, you agree to our Terms of Service and Privacy Policy

When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.

When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.

When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.

- 98% accuracy study help
- Covers math, physics, chemistry, biology, and more
- Step-by-step, in-depth guides
- Readily available 24/7